The suffragist playbook : your guide to changing the world - Robb, Lucinda, 1968-; Roberts, Rebecca Boggs (Candlewick Press, 2020)
Presents a history of the women's fight for the right to vote in the United States focusing on the strategies the suffragists used in order to bring attention to their cause including protests, petitions, speeches, writing articles, and lobbying.